1996
DOI: 10.1080/00039896.1996.9936030
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Oncologic Nurses to Methotrexate in the Treatment of Osteosarcoma

Abstract: Methotrexate is a therapeutic agent used widely for osteosarcoma. We used an extremely sensitive high-performance liquid-chromatography assay to evaluate 112 urine samples obtained from 28 hospital employees during high-dose therapy with methotrexate and during routine care of patients. The highest cumulative urinary excretion was observed when methotrexate infusions were handled in a workbench from which a portion of filtered air was emitted into the room. Remarkable urine contaminations were identified for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 17 publications
2
19
0
2
Order By: Relevance
“…Nurses exposed to chemotherapeutic agents have been found to have high concentrations of these drugs in their urine [Stellman and Zoloth, 1986;Mader et al, 1996]. Health care workers who do not have direct contact with anticancer agents may also be exposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses exposed to chemotherapeutic agents have been found to have high concentrations of these drugs in their urine [Stellman and Zoloth, 1986;Mader et al, 1996]. Health care workers who do not have direct contact with anticancer agents may also be exposed.…”
Section: Discussionmentioning
confidence: 99%
“…Health care workers who do not have direct contact with anticancer agents may also be exposed. Mader et al [1996] showed that concentrations of drugs can be detected in urine of those present in the room in which infusions were prepared, and among nurses who cared for patients who received chemotherapy. Drug concentrations were detected in the vomit and sweat of patients who received high-dose therapy; this could explain exposure among nurses who took care of infusion patients, but did not administer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a 1988 study showed that sweat collected from patients treated with cyclophosphamide and other antineoplastics showed greater mutagenicity than controls 8 h after treatment [49]. A mean concentration of methotrexate in sweat was measured as 725 ng/ml (mean maximal concentration of 1.7 mg/ml), calculated as translating into excretion of 300 mg per day through sweat [50]. Other studies provide strong indirect evidence that sweat conveys chemotherapeutics outside the body.…”
Section: Chemotherapeutics In Sweatmentioning
confidence: 99%
“…W większości prowadzonych projektów badawczych 6 cytostatyków -cyklofosfamid, metotreksat, ifosfamid, epirubicin i cisplatyna/karboplatyna -zidentyfikowano w moczu pracowników opieki medycznej, farmaceutów i personelu pielęgniarskiego, a także w moczu pracowników służby zdrowia, którzy byli narażeni na kontakt w wyniku wtórnego zanieczyszczenia powierzchni roboczych, odzieży, leków lub pojemników [12,[21][22][23].…”
Section: Wynikiunclassified
“…Jednocześnie w 104 próbkach pobranych z powierzchni narzędzi wykazano zawartość MTX wynoszącą śred-nio 28-50,8 mg/m 2 , a maksymalnie -2,5 g/m 2 . Ocena narażenia pracowników przygotowujących infuzje, personelu pomocniczego i bezpośrednio opiekującego się pacjentem oraz pracowników aptek w 28 szpitalach w Austrii wykazała, że najwyższe skumulowane stężenie MTX (112 próbek) wynosiło 1416 µg w moczu u osób podłączających i przygotowujących wlewy pacjentom [21]. Metotreksat zidentyfikowano w pocie pacjentów poddawanych chemioterapii, w średnim stęże-niu 1,7 µg/ml (N = 5).…”
Section: Wynikiunclassified